Effects of Remote Ischemic Preconditioning in Patients Undergoing Off-Pump Coronary Artery Bypass Graft Surgery - Wang, Huilin; Lyu, Yi; Liao, Qingwu; Jin, Lin; Xu, Liying; Hu, Yan; Yu, Ying; Guo, Kefang (Frontiers in Physiology, 2019)
Purpose：This study aimed to evaluate effects of remote ischemic preconditioning (RIPC) on myocardial injury in patients undergoing off-pump coronary artery bypass graft surgery (OPCABG). Methods: Sixty-five patients scheduled for the OPCABG were randomly assigned to control (n=32) or RIPC group (n=33). All patients received general anesthesia. Before the surgical incision, RIPC was induced on an upper limb with repeated five-minute ischemia and five-minute reperfusion for four times. Blood samples were collected from right internal jugular vein. Plasma levels of IL-6, IL-8, IL-10, TNF-α, cTnT, HFABP, IMA and MDA were detected at pre-operatively and 0 hour, 6 hours, 18 hours, 24 hours, 48 hours, 72 hours, and 120 hours after the surgery. Left internal mammary artery (LIMA) and great saphenous vein (GSV) was cut into 2-3 mm for Western blot analysis of Hif-1α. Results: In the present study, RIPC treatment significantly reduced plasma levels of cardiac troponin T (p=0.043), heart-type fatty acid binding protein (p=0.004), ischemia modified albumin (p=0.00013), malondialdehyde (p=0.013), as well as plasma levels of pro-inflammatory cytokines including IL-6, IL-8 and TNF-α (P=0.00054, 0.00021, 0.001, respectively). RIPC treatment significantly increased hypoxia-inducible factor-1α (p=0.00013) expression as well. Mechanical ventilation time for postoperative patients was shortened in RIPC group than those in control group (17.4 ± 3.8 h vs. 19.7 ± 2.9 h, respectively, p=0.006). Conclusions: RIPC by upper limb ischemia shortens mechanical ventilation time in patients undergoing OPCABG. RIPC treatment reduces postoperative myocardial enzyme expression and pro-inflammatory cytokine production. RIPC is a protective therapeutic approach in the coronary artery bypass graft surgery.